Morphosyntactic aspects of agrammatism in Palestinian Arabic: Findings from a Semitic language - Adam, Hisham (Revista de Investigación en Logopedia, 2023)
The present study uses a spontaneous speech task to investigate the production of morphosyntactic elements in Palestinian Arabic agrammatism (PA). Eight Palestinian-Arabic-speaking individuals with agrammatism (6 males and 2 females), diagnosed with mild to severe Broca’s aphasia, and 8 age- and gender-matched healthy speakers participated in the study. A speech sample of 100 words from each participant was transcribed and analyzed. Findings showed that substitutions, omissions, simplified sentence structure, and tense inflection errors mostly characterized Palestinian Arabic agrammatism. As for tense and agreement, the speakers with agrammatism showed more tense inflection impairments than agreement inflections. The results suggest that the individuals of PA with agrammatism had marked dissociations in producing certain types of specific morphosyntactic structures, confirming previous findings, mainly from Hebrew and Jordanian Arabic.